Adsorption of Arsenic from Water Using Aluminum-Modified Food Waste Biochar: Optimization Using Response Surface Methodology - Hashimi, Sayed Q.; Hong, Seung Hee; Lee, Chang Gu; Park, Seong Jik (Water (Switzerland), 2022)
Aluminum-impregnated food waste was selected as a filter medium for removing As(III) from aqueous solutions. The modification of food waste and its carbonization conditions were optimized using the Box–Behnken model in the response surface methodology. Pyrolysis temperature and Al content significantly influenced the As(III) adsorption capacity of aluminum-modified food waste biochar (Al-FWB), but the pyrolysis time was insignificant. Several factors affecting the adsorption capacity of the Al-FWB, including the pH, contact time, dosage, competitive anions, and reaction temperature, were studied. The low solution pH and the presence of HCO3−, SO42−, and PO43− reduced the As(III) adsorption onto Al-FWB. The pseudo-second order model showed a better fit for the experimental data, indicating the dominance of the chemisorption process for As(III) adsorption. Langmuir and Freundlich isotherm models fit the adsorption data, but the Langmuir model with a higher (R2) value showed a better fit. Hence, As(Ⅲ) was adsorbed onto Al-FWB as a monolayer, and the maximum As(Ⅲ) adsorption capacity of Al-FWB was 52.2 mg/g, which is a good value compared with the other porous adsorbents. Thus, Al-FWB is a promising low-cost adsorbent for removing As(III) from aqueous solutions and managing food waste.
Keywords: Adsorption capacities; Adsorption of arsenics; Biochar; Box-behnken models; Carbonization conditions; Filter mediums; Food waste; Optimisations; Pyrolysis temperature; Response-surface methodology; arsenic; biochar; food waste; optimization; response surface methodology